The Economic Side of Waste Sorting Problem - Tkachuk, Y. M. (My University, 2020)
Nowadays waste sorting problem is becoming increasingly vital as young generation, in particular people between 13 and 30 years old, care about the future of the planet. However, the environmental pollution caused by waste that people throw away is often overlooked. The so-called “Lviv waste crisis” of 2016 and 2017caused a serious problem for our country while creating a threat for the ecology as well. So, it is necessary to do research into the issue of waste sorting in Ukraine, and in Melitopol in particular.
Keywords: waste sorting; environmental pollution